Marta Gargallo - Effect of the Cutting Method and Transport Temperature on the Quality of Ovarian Tissue (Jornada de Jóvenes Investigadores del I3A, 2025)
Effect of the Cutting Method and Transport Temperature on the Quality of Ovarian Tissue